An inscription on the pilaster of the Antarala in the Suhaveshwar Temple - Temples of India Project Team (Jio Institute, 2024)
Seen here is an inscription on the pilaster on the right side of the antarala (vestibule or antechamber) in the Suhaveshwar Temple. The inscription is written in Sanskrit language using Devanagari script. The inscriptions state that Suhavadevi, queen of Prithviraja II, the Chahamana King in the year 1168 CE, gave donations for the construction of the temple.